Short-Term Perioperative Complications and Mortality After Total Ankle Arthroplasty in the United States. Issue 2 (April 2018) - Heida, Kenneth A.; Waterman, Brian; Tatro, Eric; Bader, Julia; McCoy, Andrew C.; Rensing, Nicholas; Orr, Justin
This study sought to identify patient and operative demographics associated with 30-day perioperative complications in patients undergoing total ankle arthroplasty as recorded in the National Surgical Quality Improvement Project database. Complications were divided into local and systemic and further subcategorized as major and minor. A total of 404 patients underwent total ankle arthroplasty between 2007 and 2014 as captured in the National Surgical Quality Improvement Project database. The overall complication rate was 2.4% with 0.5% mortality and 0.2% infection rate. Length of hospital stay, both as an end point at >5 days and as a continuous variable, was associated with overall complications (odds ratio [OR] = 9.90, P = .002 and OR = 1.52, P = .006, respectively). Patient characteristics that predicted perioperative morbidity included presence of 3 or comorbidities (OR = 8.48, P = 0.038), American Society of Anesthesiologists class III, and history of previous cardiac surgery (OR = 12.22, P = .033). Correct patient selection is imperative in achieving improved outcomes and those that are at risk for complications should be counseled as such. Levels of Evidence: Level III: Database case control study